Pengaruh Pemberian Variasi Konsentrasi Thiamin HCL Terhadap Seedling Phalaenopsis Var. Happy Valentine - Handini; M. Anas Dzakiy; Eny Hartadiyati (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2024)
Phalaenopsis var. Happy Valentine orchid is a plant with a growth and flowering process of approximately 1-2 years. Generally, orchids can bloom in about 9-12 months. Optimal concentrations of Thiamine HCl (vitamin B1) are required to support the vegetative growth of Phalaenopsis var. Happy orchids. This research aims to determine the effect and the best concentration of vitamin B1 among 1ml, 2ml, and 3ml on the vegetative growth, including leaf span, root quantity, leaf width, and length of young leaves of Phalaenopsis var. Happy Valentine seedlings. The method used was a Completely Randomized Design (CRD), with treatment factors being the concentration of vitamin B1 and Growmore fertilizer, comprising four treatment levels and six replications, namely V0 = 2gr/L Growmore fertilizer, V1 = 2gr/L Growmore fertilizer + 1ml B1, V2 = 2gr/L Growmore fertilizer + 2ml B1, dan V3 = 2gr/L Growmore fertilizer + 3ml B1. This research used 24 Phalaenopsis var. Happy Valentine orchid seedlings as research samples. The data were analyzed using ANOVA with a significance level 0.05 and subsequently subjected to Duncan's test. The results indicate that vitamin B1 significantly affects leaf span, length of young leaves, and the quantity of roots in Phalaenopsis var. Happy Valentine.